Phylogenetic conservatism in the relationship between functional and demographic characteristics in Amazon tree taxa - Sanchez-Martinez, P.; Dexter, K.G.; Draper, F.C.; Baraloto, C.; Leão do Amaral, I.; de Souza Coelho, L.; de Almeida Matos, F.D.; de Andrade Lima Filho, D.; Salomão, R.P.; Wittmann, F.; Castilho, C.V.; de Jesus Veiga Carim, M.; et al. (British Ecological Society, 2025)
1. Leaf and wood functional traits of trees are related to growth, reproduction, and survival, but the degree of phylogenetic conservatism in these relationships is largely unknown. In this study, we describe the variability of strategies involving leaf, wood and demographic characteristics for tree genera distributed across the Amazon Region, and quantify phylogenetic signal for the characteristics and their relationships.
2. Leaf and wood traits are aligned with demographic variables along two main axes of variation. The first axis represents the coordination of leaf traits describing resource uptake and use, wood density, seed mass, and survival. The second axis represents the coordination between size and growth. Both axes show strong phylogenetic signal, suggesting a constrained evolution influenced by ancestral values, yet the second axis also has an additional, substantial portion of its variation that is driven by functional correlations unrelated to phylogeny, suggesting simultaneously higher evolutionary lability and coordination.
3. Synthesis. Our results suggest that life history strategies of tropical trees are generally phylogenetically conserved, but that tree lineages may have some capability of responding to environmental changes by modulating their growth and size. Overall, we provide the largest-scale synopsis of functional characteristics of Amazonian trees, showing substantial nuance in the evolutionary patterns of individual characteristics and their relationships.